Adenosine reagentless electrochemical aptasensor using a phosphorothioate immobilization strategy - Ceretti, Helena (2010)
This work deals with the characterization of a phosphorothioate anchoring strategy for aptamer molecules linked to gold, in the context of electrochemical sensors, using adenosine aptamer as model system. Surface density of immobilized phosphorothioate oligonucleotide sequences has been explored for a range of oligonucleotide concentrations (0.055 -55 μM), finding a consequent variation of molecular surface density (3.5×1011 -2.8 ×1013 molecules/cm2). Most suitable aptamer concentration for adenosine recognition was also explored and found to be around 5.5 μM. As proof of concept of phosphorothioate strategy, electrochemical response to adenosine concentration was measured using a ferrocene-labeled oligonucleotide sequence, and phosphorothioate anchoring thermal stability was compared to thiol immobilization. © 2010 Wiley-VCH Verlag GmbH&Co. KGaA, Weinheim.